Like a brother, like a lover : male homosexuality in the American novel and theatre from Herman Melville to James Baldwin - Sarotte, Georges-Michel (New York: Anchor Press, 1978)
"Georges-Michel Sarotte Fonds Suzan Daniel (FSD)"